Tabarak Methode as a Means of Da'wa to Make it Easier for Children to Memorize The Quran - Musyafaah, Nur Lailatul; Masyhud, Fathin (Proceedings of International Conference on Da'wa and Communication, 2021)
Teaching children about reading and memorizing the Quran is part of da'wa to children. Today many Muslim families who want their children can be memorizers of the Quran. Therefore, various kinds of tahfiz methods have been sprung for children, including the Tabarak method. This research investigates how the Tabarak method becomes a means of da'wa to facilitate tahfiz al-Quran for children. This research uses a qualitative approach with this type of literature study research. In general, the findings of this study show that the Tabarak method can be used as a means of da'wa for children to memorize the Quran quickly. That is indicated by the positive reception of children who perform tahfiz with the Tabarak method. In addition to many parents who accompany their children can also memorize the Quran as memorized by their children. With the support of the family, children can memorize the Quran and live a better life because the Quran guides what they learn. The training was held to expand the spread of the Tabarak method, especially for facilitators of tahfihz Markaz, managers, and parents. The promotion of Tabarak method is also done through social media such as WhatsApp groups, Facebook, and Instagram.